Regulatory framework for the Brazilian electricity matrix - Ítalo Freire, Anderson; Fontgalland, Isabel (Latin American Journal of Energy Research, 2022)
Currently, the need to preserve the environment and its components has taken over the debates at all levels that could be covered. Dialogue around this theme is essential, given that the effects of extreme exploitation of the environment are strongly visible in all aspects. Thus, the objective of this article is to present the case of wind farms in Brazil through their regulatory frameworks, from the implementation of Proeólica in 2002 to the elaboration of the regulation of offshore wind energy in 2022. This article is a case study with four sections. In the first one, there is a description of the electricity matrix in Brazil, highlighting the most representative sources; in the second section there is a description of the national wind sector, highlighting the extension of the parks and the evolution of their installed capacity. In the third section there is a description of the energy regulatory process, considering Proeólica, Proinfa, and PL 567/2021. Finally, the article discusses the results observed in this article.Keywords: Brazil, Wind power, Regulatory Framework